Ultrafast Pump‐Probe Spectroscopy—A Powerful Tool for Tracking Spin‐Quantum Dynamics in Metal Halide Perovskites. Issue 8 (10th June 2021) - Chen, Zhi; Dong, Guoping; Qiu, Jianrong
Abstract: Ultrafast pump‐probe spectroscopy provides a powerful tool for deep insight into sophisticated electron–hole dynamics for materials development and devices optimization, particularly for emerging metal halide perovskites (hereafter, termed perovskites), due to their great potentials for optoelectronic and photonic applications in solar cells, light‐emitting diodes, photodetectors, and lasers. Recently, flourishing spin‐related photophysical phenomena (such as, Rashba effect, optical Stark effect, and magnetooptical effect) in perovskites and their relevant devices have experimentally been observed, attributed to huge spin‐orbital coupling effect and strong interaction of electron–photon in perovskites. However, fundamental understanding of spin‐dependent photophysics in perovskites is still at its nascent stage. In recent few years, circularly‐polarized ultrafast pump‐probe technique has pushed burgeoning development of spin‐selective photophysics in perovskites for spintronic device applications. Nevertheless, few review papers summarize this emerging field systematically, completely, and insightfully. Herein, to evoke broader attraction and research interest, recent advances in spin‐quantum dynamics in perovskites revealed by circularly‐polarized pump‐probe technique are reviewed: from the fundamentals and theories of circularly‐polarized ultrafast pump‐probe transient absorption and time‐resolved Faraday rotation spectroscopy; to the recent enlightening works on spin relaxation dynamics, spin‐selective exciton optical Stark effect, magnetic spin effect, and spin polarization dynamics. Finally, current challenges and perspectives are given. Abstract : Ultrafast pump‐probe spectroscopy provides a powerful tool for deep insight into sophisticated electron–hole dynamics for materials development and devices optimization, in particular of superstar "metal halide perovskites." Here, a comprehensive review is given on the recent progress in spin‐quantum dynamics in perovskites revealed by circularly‐polarized ultrafast pump‐probe technique, from fundamentals and theories, to recent enlightening works, to perspectives.